Wastewater-powered high-value chemical synthesis in a hybrid bioelectrochemical system - Wu, Ranran; Yu, Yang-Yang; Wang, Yuanming; Wang, Yan-Zhai; Song, Haiyan; Ma, Chunling; Qu, Ge; You, Chun; Sun, Zhoutong; Zhang, Wuyuan; Li, Aitao; Li, Chang Ming; et al. (iScience, 2021)
A microbial electrochemical system could potentially be applied as a biosynthesis platform by extracting wastewater energy while converting it to value-added chemicals. However, the unfavorable thermodynamics and sluggish kinetics of in vivo whole-cell cathodic catalysis largely limit product diversity and value. Herein, we convert the in vivo cathodic reaction to in vitro enzymatic catalysis and develop a microbe-enzyme hybrid bioelectrochemical system (BES), where microbes release the electricity from wastewater (anode) to power enzymatic catalysis (cathode). Three representative examples for the synthesis of pharmaceutically relevant compounds, including halofunctionalized oleic acid based on a cascade reaction, (4-chlorophenyl)-(pyridin-2-yl)-methanol based on electrochemical cofactor regeneration, and l-3,4-dihydroxyphenylalanine based on electrochemical reduction, were demonstrated. According to the techno-economic analysis, this system could deliver high system profit, opening an avenue to a potentially viable wastewater-to-profit process while shedding scientific light on hybrid BES mechanisms toward a sustainable reuse of wastewater. [Display omitted] •A microbe-enzyme hybrid bioelectrochemical system was developed•Wastewater-powered production of high-value chemicals was achieved with the hybrid BES•High system profit for wastewater-to-chemical production was accomplished•This hybrid BES is promising for techno-economic feasible wastewater-to-profit process Materials in biotechnology, Materials science, Electrochemistry, Bio-electrochemistry